2022
DOI: 10.1002/hep.32802
|View full text |Cite
|
Sign up to set email alerts
|

TP53 R249S mutation in hepatic organoids captures the predisposing cancer risk

Abstract: Background and Aims: Major genomic drivers of hepatocellular carcinoma (HCC) are nowadays well recognized, although models to establish their roles in human HCC initiation remain scarce. Here, we used human liver organoids in experimental systems to mimic the early stages of human liver carcinogenesis from the genetic lesions of TP53 loss and L3 loop R249S mutation. In addition, chromatin immunoprecipitation sequencing (ChIP‐seq) of HCC cell lines shed important functional insights into the initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…This phenomenon promoted glycolytic metabolic intensity and cell proliferation in HCC. It was also confirmed that the frequency of the R249S mutation in TP53 revealed the risk of HCC, and TP53 deletion increased the viability of hepatocellular carcinoma cells and the trend of poor prognosis ( Lam et al, 2022 ). Interestingly, the C3 isoform might be a TTN mutation-driven molecular subtype that exhibited a high mutational profile.…”
Section: Discussionmentioning
confidence: 70%
“…This phenomenon promoted glycolytic metabolic intensity and cell proliferation in HCC. It was also confirmed that the frequency of the R249S mutation in TP53 revealed the risk of HCC, and TP53 deletion increased the viability of hepatocellular carcinoma cells and the trend of poor prognosis ( Lam et al, 2022 ). Interestingly, the C3 isoform might be a TTN mutation-driven molecular subtype that exhibited a high mutational profile.…”
Section: Discussionmentioning
confidence: 70%
“…Tumorigenic transformation typically requires additional driver mutations or enforced microenvironmental changes [35]. Since this model was derived from adult human paired HCC tumor and adjacent non-tumoral liver tissues, compared to our iPSC-derived eHEPO model, the cells may exhibit slightly different responses due to differences in stemness repository (adult-fetal stem cells, respectively) and cell composition [74].…”
Section: Discussionmentioning
confidence: 99%
“…HCC PDO culture was performed as in the previous study. [ 7 , 26 ] Samples were minced and digested with 2 mg mL −1 collagenase II (GIBCO) at 37 °C for 1 h. Then, pellets were filtered through a 70‐µm cell strainer (Falcon), mixed with Matrigel (Corning), and cultured in HCC organoid culture medium: Advanced DMEM/F12 medium (GIBCO) was supplemented with 1% Penicillin/Streptomycin (Biological Industries), 1% L‐Glutamine (STEMCELL), 10 m m HEPES (GIBCO), 1:50 B27 supplement (without Vitamin A, GIBCO), 1:100 N2 supplement (GIBCO), 1.25 m m n‐Acetyl‐L‐cysteine (Sigma), 10 m m nicotinamide (Sigma), 50 ng mL −1 recombinant human R‐spondin (Rspo)‐1 (Novoprotein), 50 ng mL −1 recombinant human Epidermal growth factor (EGF) (Novoprotein), 50 ng mL −1 recombinant human Fibroblast growth factor (FGF) 10 (Novoprotein), 50 ng mL −1 recombinant human Hepatocyte growth factor (HGF) (Novoprotein), 10 ng mL −1 Noggin (Novoprotein), 5 µ m A8301 (Abmole) and 10 µ m Y27632 (Abmole). Organoids were digested using collagenase II, washed, and cultured in HCC organoid culture medium with Matrigel for subsequent culture.…”
Section: Methodsmentioning
confidence: 99%
“…Patient‐derived organoids (PDO) are 3D‐culture models which can proliferate in vitro and retain some key characteristics of the original tumor specimens, [ 7 ] therefore displaying promising potential in application on drug screening and precision therapy. [ 8 ] However, their potential to predict clinical outcomes in patients is still unclear, and the in vitro evaluation model for immunotherapeutic drugs remains lacking.…”
Section: Introductionmentioning
confidence: 99%